Leadership in Action : a Question of Leadership - Is There a Difference Between Youth Leaders and Adult Leaders? - Liu, Jerusha (Center for Creative Leadership, 2006)
The question of whether there is a difference between the leadership style of youths and that of adults can be answered by looking at the opinions of young people themselves.